Bit Manipulation: Conditional Statement using Bit-wise operators with C++ - Nafi'ah, Rahmawati; Kurniawan, Wakhid; Setiawan, Johan; Umam, Khoirul (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
All of information that manipulated by a computer is represented in the form of bits, so in the programming language it is necessary to understand bitwise operations at the first. This paper aims to create a concept of making Conditional Statements with Bitwise operators in C ++. By doing so, we hope that people is easy to understand the operation behind conditional statements. A conditional operator is also known as a ternary operator. It takes three operands. A conditional operator is closely related with if else statement. The method used is a literature study studying the bit manipulation algorithm in the C ++ language. The results obtained are a function using bitwise operations in C ++ that implement conditional statements.